2017
DOI: 10.1111/cdev.12810
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Transfer Deficit: Contextual Mismatch, Proactive Interference, and Working Memory Affect Toddlers’ Video‐Based Transfer

Abstract: Researchers tested the impact of contextual mismatch, proactive interference, and working memory (WM) on toddlers' transfer across contexts. Forty-two toddlers (27-34 months) completed four object-retrieval trials, requiring memory updating on Trials 2-4. Participants watched hiding events on a tablet computer. Search performance was tested using another tablet (match) or a felt board (mismatch). WM was assessed. On earlier search trials, WM predicted transfer in both conditions, and toddlers in the match cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 74 publications
1
12
0
1
Order By: Relevance
“…As a result, children with a relatively poor working memory capacity (e.g., relatively younger children) are more likely to have difficulties in transfer. Indeed, 2-year-olds' performance on a working memory task predicted whether they would transfer information from a video to actual objects, even after controlling for the children's age and receptive vocabulary (28). This finding supports the hypothesis that transfer across contexts (e.g., from screen images to actual objects) is demanding cognitively and requires substantial cognitive resources.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…As a result, children with a relatively poor working memory capacity (e.g., relatively younger children) are more likely to have difficulties in transfer. Indeed, 2-year-olds' performance on a working memory task predicted whether they would transfer information from a video to actual objects, even after controlling for the children's age and receptive vocabulary (28). This finding supports the hypothesis that transfer across contexts (e.g., from screen images to actual objects) is demanding cognitively and requires substantial cognitive resources.…”
supporting
confidence: 60%
“…However, toddlers can also learn from interactive media that do not involve video chats with an actual person. Specifically, toddlers also learned more from interactive screen media (versus noninteractive video) when they played a computer game or used a touchscreen application .…”
Section: Does Interactivity Support or Hinder Learning From Digital Mmentioning
confidence: 99%
“…In addition, video memories may mismatch future in vivo situations, making transfer more difficult (Barr, 2010). Overcoming these challenges may be cognitively demanding and require more working memory than using information learned face to face (Barr et al, 2016; Choi, Kirkorian, & Pempek, 2018; Kirkorian, 2018).…”
Section: Causes Of the Video Deficitmentioning
confidence: 99%
“…Hughes and Ensor (2007) reported that children were asked to help the experimenter hide the stickers (see also Huber, Yeates, Meyer, Fleckhammer, & Kaufman, 2018). In prior studies, some researchers adopted a self‐ordered protocol (Beck et al., 2011; Müller, Liebermann‐Finestone, Carpendale, Hammond, & Bibok, 2012; Roman, Ensor, & Hughes, 2016), while others adopted an experimenter‐ordered protocol (Blakey & Carroll, 2018; Blakey et al., 2016; Choi, Kirkorian, & Pempek, 2017; Johansson, Marciszko, Brocki, & Bohlin, 2015). In the present study, we opted for a self‐ordered version of the task.…”
Section: Introductionmentioning
confidence: 99%